Secular trends in end-stage renal disease requiring dialysis in Manitoba, Canada: a population-based study - Komenda, Paul (CMAJ Open, 2015)
BACKGROUND: End-stage renal disease (ESRD) requiring dialysis is expensive and is associated with disproportionately poor health outcomes and quality of life. Understanding regional long-term secular trends in the incidence and prevalence of dialysis will allow for the alignment of appropriate and efficient delivery of care. The primary objective of this study was to describe long-term secular and geographic trends in ESRD over a 22-year period in a single-provider Canadian health care setting. METHODS: Using a previously validated case definition, we described the annual incidence and prevalence of ESRD in Manitoba from 1989 to 2010, stratified by age, sex and geographic location within the province. RESULTS: We searched more than 1.2 million records within the Manitoba Health repository. We identified 9489 patients in the Manitoba Health Physician Claims database with at least 1 claim for dialysis from 1989 through Mar. 31, 2010. Using the case definition of any 2 dialysis treatment claims, the total annual incidence of ESRD increased 2.5-fold from 15.8 to 40.2 per 100 000 during the study period. Of note, the northern rural portions of the province saw a 12-fold unadjusted increase in ESRD, from 8.1 per 100 000 in 1989 to 96.3 per 100 000 in 2009. INTERPRETATION: The incidence and prevalence of ESRD is increasing in Manitoba, most notably in the north of the province. Innovative interventions, such as primary screening and treatment initiatives, should specially target northern rural regions.